Single-nucleotide-polymorphism-panel population-genetics approach based on the 1000 genomes database and elite soccer players - Monnerat, G.; Maior, A. S.; Tannure, M.; Back, L. F. K.; Santos, C. G. M. (International Journal of Sports Physiology and Performance, 2019)
Purpose: Soccer is one of the most popular sports worldwide, a physical activity of great physiological demand and complexity. Currently, numerous trials involving physiological responses such as hypertrophy, energy expenditure, vasodilation, cardiac output, VO2max, and recovery have supported the possibility of genomic predictors` affecting performance. In a complementary way to association studies with single nucleotide polymorphisms (SNPs), the objective was to evaluate if the use of population genetics data from human-genomics databases can provide information for a better understanding of the relationship between heritability and sport performance. Methods: The study included 25 healthy male professional soccer players (25.5 [4.3] y, 177.4 [6.4] cm, 76.4 [6.4] kg, body fat 10.5% [4.3%]) from the Brazilian first-division soccer club. Anthropometric measurements and field and isokinetic tests were performed to evaluate performance and physiologic parameters of subjects. Moreover, 10 genetic polymorphisms previously related to performance were genotyped. The genotypes of the same polymorphisms were obtained for 2504 individuals from the populations deposited in the 1000 Genomes database. A principal-component analysis and matrix genetic-distances approach (Fst) were evaluated. Results: As expected, the admixture Brazilian population has numerous genetic similarities with the European and American populations from genomic databases. Although the African component is absolutely recognized in genomes from the Brazilian population, using the specific performance-related SNPs, surprisingly the African population was one of the most genetically distant of the players (P<.00001). Conclusions: The early results suggest a selective pressure on genes of elite soccer players, possibly related simultaneously to physical-performance, environmental, cognitive, and sociocultural aspects.